calcular:

2 a la 3 + 5 a la 2 =

(1/2) a la 2 =

(5 sobre 6) a la 2 =

2 a la 4 + 4 a la 2 =

(-2 a la 3) a la 2 =

(7 + 3) a la 3 =

(3) a la 3 =

(5/7) a la 2 =

[(2 sobre 3) a la 2 ] a la 3 =

(2/5) a la 4 =

(-2) a la 1 + (-2) a la 2 + (-2) a la 3 + (-2) a la 4 + (-2) a la 0 =

1

Respuestas

2012-09-25T01:44:01+02:00

2 a la 3+5 a la 2= 8+25= 33

1sobre2 a la 2= 1sobre 4

5sobre6 a la 2= 25 sobre 36

2 a la 4 +4 a la 2= 16+16 =32

(2 a la 3)a la 2= -8 a la 2= 64

3 a la 3= 27

5sobre7 a la 2= 25sobre49

(2sobre3a la 2)a la 3= 84sobre729=28sobre243

2sobre5a la 4= 16 sobre 625

(-2) a la 1 + (-2) a la 2 + (-2) a la 3 + (-2) a la 4 + (-2) a la 0 =27